Mercury Azides and the Azide of Millon's Base1. Issue 41 (26th August 2013) - Lund, Henrik; Oeckler, Oliver; Schröder, Thorsten; Schulz, Axel; Villinger, Alexander
<x xml:space="preserve">Abstract</x> Always look on the bright azide of life: The synthesis of Millon's base azido salt [Hg2N]N3, and the metastable β‐Hg(N3)2, along with their full characterization is possible for the first time and closes an open gap in azide chemistry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>